Characterization of PolyMUMPs-based in-plane electromagnetic actuator - Ahmed, M.G. (American Institute of Physics Inc., 2016)
This paper presents a synopsis of the design and fabrication of an in-plane electromagnetic actuator using Polysilicon Multi-Users MEMS Process (PolyMUMPs). The electromagnetic actuator is driven by Lorentz force. This article is based on the premise that the proportionality of Lorentz force to magnetic field and driving current controls lateral displacement. The fabricated actuator consists of two plates; moving plate supported by four beams and a stationary plate in order to form a capacitor setup for sensing. This work experimentally demonstrates the actuation of the device using low frequencies of 0.5 Hz, 1 Hz and 2Hz. The characterization of the micro actuator using a Leica optical microscope showed a displacement exceeding 8 Î¼m. This displacement is attained with a magnetic field of 20mT and applied current of approximately 5 mA. Â© 2016 Author(s).